2018
DOI: 10.3389/fnagi.2018.00386
|View full text |Cite
|
Sign up to set email alerts
|

Age Effects on Spatiotemporal Dynamics of Response Inhibition: An MEG Study

Abstract: Inhibition, the ability to suppress irrelevant information, thoughts or movements, is crucial for humans to perform context-appropriate behaviors. It was suggested that declined cognitive performance in older adults might be attributed to inhibitory deficiencies. Although previous studies have shown an age-associated reduction in inhibitory ability, the understanding regarding its cortical spatiotemporal maps remained limited. Thus, we used a whole-head magnetoencephalography (MEG) to elucidate the age effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 72 publications
(108 reference statements)
0
12
0
Order By: Relevance
“…In contrast to our previous findings, we did not find any significant differences between high- and low-performing older adults. Our previous results from a visual go/no-go task indicated that high performers exhibited greater left frontal activation than low performers in an older adult group [ 22 ]. The experimental methodology of the two studies is similar apart from the type of stimulus used (visual versus auditory).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to our previous findings, we did not find any significant differences between high- and low-performing older adults. Our previous results from a visual go/no-go task indicated that high performers exhibited greater left frontal activation than low performers in an older adult group [ 22 ]. The experimental methodology of the two studies is similar apart from the type of stimulus used (visual versus auditory).…”
Section: Discussionmentioning
confidence: 99%
“…We recruited 20 younger adults (10 of whom were females; mean age 24.4 years) and 20 healthy community-dwelling older adults (12 of whom were females; mean age 62.6 years) as participants in this study. The majority of participants were sampled from our previous investigation [ 22 ]. Based on a self-report, all participants were right-handed; had no history of neurological or psychological disorders; had normal hearing, and had normal or corrected-to-normal (with contact lenses) vision.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This network consists of several right-lateralized frontoparietal regions [15][16][17], including the inferior frontal gyrus (IFG), insula, supplementary motor area (SMA), anterior cingulate cortex (ACC), and inferior and superior parietal lobules (IPL and SPL), of which the right IFG plays a prominent role [18][19][20][21]. Research using magnetoencephalography (MEG), which is sensitive to the timing of neural activity [22], has illustrated that these regions appear to be maximally active between 200 and 400 ms, after stimulus onset [23][24][25]. Electroencephalographic (EEG) studies have also revealed that peaks in event-related potentials at around 200 and 300 ms are associated with conflict monitoring and motor inhibition, respectively [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%